A high CTI high thermal conductivity epoxy glass fiber cloth based laminate and preparation method thereof
By using specific resin systems and polydopamine-modified nanoparticles in the epoxy fiber cloth base laminate, a three-dimensional mesh structure is formed, which solves the problems of poor thermal conductivity, insufficient heat resistance and poor dielectric performance of the existing substrate, and achieves the improvement of high CTI, high thermal conductivity and low dielectric performance.
Patent Information
- Application Number
- CN202411960955.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The existing epoxy resin/glass fiber cloth composite substrates have poor thermal conductivity, insufficient heat resistance and poor dielectric performance, making it difficult to meet the requirements of high CTI, high thermal conductivity, low dielectric loss and high strength.
A phenoxy resin with a molecular weight of 30,000 to 50,000 was used to form a resin system, and a high CTI high thermal conductivity epoxy fiber cloth base laminate was prepared by co-crosslinking reaction.
It has achieved performance improvements such as high CTI (600v), excellent heat resistance, high thermal conductivity (thermal conductivity can reach 3.06W/m.k) and low dielectric (the minimum dielectric constant Dk is 3.0, and the minimum dielectric loss Df is 0.002), and at the same time, it has improved strength (the maximum peel strength is 3.24N/mm, and the maximum bending strength is 315.8MPa).
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic materials, and in particular to a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate and a preparation method thereof. Background Art
[0002] Substrates play an extremely important role in the entire electronic packaging field. Substrates mainly provide mechanical support and protection for chips and components, as well as heat dissipation and insulation. The performance of the substrate affects the level of IC manufacturing.
[0003] Epoxy resin / glass fiber cloth composite substrates are widely used in packaging carrier substrate materials due to their low cost, excellent processability, good dimensional stability and adhesion. However, epoxy resin and glass fiber cloth have poor thermal conductivity, and also have disadvantages such as insufficient heat resistance and poor dielectric properties.
[0004] How to develop an epoxy glass fiber cloth-based laminate with high CTI, high thermal conductivity, low dielectric loss and high strength is a technical problem that urgently needs to be solved.
[0005] Based on this, the present invention designs a carrier board for HDI process and its preparation method and application to solve the above problems. Based on this, the present invention designs a high CTI high thermal conductivity epoxy glass fiber cloth based laminate and its preparation method to solve the above problems. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate and a preparation method thereof.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A high CTI high thermal conductivity epoxy glass fiber cloth-based laminate, comprising: a phenoxy resin with a molecular weight of 30,000 to 50,000, a fluorinated polyimide, a brominated epoxy resin and EPDM rubber to form a resin system, polydopamine-modified nanoparticles are added to the resin system as a filler, and a cross-linking curing agent and an accelerator are added to make glue; then, the glue is impregnated with glass fiber cloth to obtain a prepreg, and the prepreg and copper foil are stacked and pressed to obtain a high CTI high thermal conductivity epoxy glass fiber cloth-based laminate;
[0009] The cross-linking curing agent is prepared by mixing paraformaldehyde and dicyclopentadiene resin in a ratio of 1:0.5-0.8;
[0010] The polydopamine modified nanoparticles include the following raw materials in parts by weight: 350-400 parts of dopamine hydrochloride, 48-70 parts of dextran, 55-83 parts of nano zinc oxide, and 100-110 parts of carbon nanotubes.
[0011] Furthermore, the glue comprises the following raw materials in parts by weight: 500 to 625 parts of a phenoxy resin with a molecular weight of 30,000 to 50,000, 45 to 85 parts of a fluorinated polyimide, 102 to 165 parts of a brominated epoxy resin, 50 to 70 parts of EPDM rubber, 165 to 178 parts of polydopamine-modified nanoparticles, 8 to 13 parts of a cross-linking curing agent, 5 to 10 parts of an accelerator, and 800 to 980 parts of a solvent.
[0012] Furthermore, the preparation method of the polydopamine modified nanoparticles is as follows: nano zinc oxide, carbon nanotubes and dextran are mixed, ball milled at 50-80° C. for 1-2 hours, and impurity gases are removed by vacuuming; the ball milled product is placed in 300-400 parts of deionized water, pressurized to 1-1.5 MPa, maintained for 1-2 minutes, and then restored to normal pressure, then reduced to 0.3-0.5 MPa, maintained for 5-8 minutes, and then restored to normal pressure, and then heated to 65-84° C. by microwave-assisted heating, Tris-HCl and dopamine hydrochloride are added, and the pH value is adjusted to 8.3-9.1 with NaOH; heated and stirred at 55-65° C. for 4-8 hours, and the polydopamine modified nanoparticles are obtained after centrifugal washing and drying.
[0013] In order to better achieve the purpose of the present invention, the present invention also provides a method for preparing a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate, comprising the following steps:
[0014] Step 1: Prepare glue;
[0015] (1) Preparation of polydopamine-modified nanoparticles
[0016] The nano zinc oxide, carbon nanotubes and dextran are mixed, ball milled at 50-80°C for 1-2h, and impurity gases are removed by vacuuming; the ball milled product is placed in 300-400 parts of deionized water, pressurized to 1-1.5MPa, maintained for 1-2min and then restored to normal pressure, then reduced to 0.3-0.5MPa, maintained for 5-8min and then restored to normal pressure, then heated to 65-84°C by microwave-assisted heating, 400 parts of Tris-HCl and dopamine hydrochloride are added, and the pH value is adjusted to 8.3-9.1 with NaOH; heated and stirred at 55-65°C for 4-8h, and polydopamine modified nanoparticles are obtained after centrifugal washing and drying;
[0017] (2) injecting the solvent into the reaction kettle and starting stirring;
[0018] (3) Resin feeding tank: Phenoxy resin with a molecular weight of 30,000 to 50,000, fluorinated polyimide, brominated epoxy resin and EPDM rubber are injected into the reaction kettle;
[0019] (4) Cross-linking reaction: Add the cross-linking curing agent and accelerator into the reaction kettle, control the reaction temperature at 55-60° C., continue to stir at high speed for 1.5-2 hours, then raise the temperature to 60-65° C., continue to stir at high speed for 1-1.5 hours, so that the cross-linking reaction with the above-mentioned resin can be fully produced;
[0020] Step 2: Impregnation;
[0021] The glass fiber cloth is immersed in the prepared glue, and then dried to evaporate the excess solvent and further react the resin with the cross-linking curing agent to obtain a prepreg with appropriate parameters;
[0022] Step 3: Surface pretreatment of the prepreg;
[0023] The semi-cured sheet is placed in an alkaline treatment solution and ultrasonically treated for 1 to 2 hours at a temperature of 25 to 30°C and normal pressure, then washed with water and dried;
[0024] Step 4: Stacking;
[0025] Stack multiple prepregs, cover one or both sides with copper foil, and send them into a hot press after assembly;
[0026] Step 5: Pressing;
[0027] Use a hot press to press together, use high temperature to melt the resin in the prepreg, and drive out the bubbles under high pressure, so that the resin gradually hardens and adheres to the copper foil.
[0028] Furthermore, step 6: cutting is also included.
[0029] Furthermore, step 2 is specifically as follows: placing the electronic-grade glass fiber cloth on the cloth rack of the impregnation machine, controlling its advancement by tension, passing the electronic-grade glass fiber cloth through the impregnation tank with glue, and the electronic-grade glass fiber cloth soaked in glue enters the oven, controlling the oven temperature to 180-200° C., and obtaining a semi-cured sheet after drying.
[0030] Furthermore, the pressing temperature of the hot press is 210-230° C., and the pressure is 2.3-3.5 MPa.
[0031] Furthermore, step 6 is specifically as follows: trimming off the edge material of the laminated substrate, and then obtaining a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate after the laminate passes the appearance and thickness inspections.
[0032] Furthermore, the method further comprises step (5) stopping the machine to measure S / G: extracting a proper amount of glue liquid and testing whether the S / G of the glue is between 230 and 270S. If so, the glue quality is qualified.
[0033] In order to better achieve the purpose of the present invention, the present invention also provides a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate prepared according to the preparation method.
[0034] Compared with the prior art, the invention has the following beneficial effects: firstly, nano zinc oxide, carbon nanotubes and dextran are mixed and ball-milled, and further fusion of the materials is promoted by first pressurizing and then reducing pressure, and then reacting with Tris-HCl buffer and dopamine hydrochloride under alkaline conditions, dopamine self-polymerizes under alkaline conditions and modifies nanoparticles, and co-crosslinking reactions occur between polydopamine on the surface of the nanoparticles and the resin system, and between the resin systems, to form a three-dimensional network crosslinking structure; an accelerator and an improved crosslinking curing agent react with the resin system and the polydopamine-modified nanoparticles, and the improved crosslinking curing agent reacts with the active functional groups of the polydopamine, and a dicyclopentadiene structure is introduced at the same time, so as to further promote the crosslinking reaction between the resin system and the polydopamine, and after curing, it is beneficial to further enhance the strength of the three-dimensional network structure and the uniformity of filler distribution, and improve the heat resistance, thermal conductivity and other properties. The epoxy glass fiber cloth-based laminate prepared by the present invention meets the requirements of high CTI (600v), excellent heat resistance, high thermal conductivity (thermal conductivity can reach 3.06W / mk) and low dielectric (dielectric constant Dk is minimum 3.0, dielectric loss Df is minimum 0.002), and has high strength (peel strength is maximum 3.24N / mm, bending strength is maximum 315.8MPa). DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Phenoxy resin with molecular weight of 50,000 to 80,000: has good heat resistance, electrical insulation, adhesion and chemical corrosion resistance;
[0037] Fluorinated polyimide: The fluorine atoms in its molecular structure can reduce the dielectric constant of the material.
[0038] Brominated epoxy resin: good heat resistance;
[0039] EPDM rubber: has good insulation properties;
[0040] Polydopamine modified nanoparticles: Dopamine self-polymerizes and modifies nanoparticles in an alkaline environment. The polydopamine on the surface of the nanoparticles is cross-linked with the resin system to form a three-dimensional network structure.
[0041] Cross-linking curing agent: paraformaldehyde, dicyclopentadiene resin; react with the active functional groups of polydopamine, and introduce dicyclopentadiene structure to promote the cross-linking reaction between the resin system and polydopamine;
[0042] Accelerator: 2E4MZ, catalytic effect, initiation and acceleration of curing speed;
[0043] Solvent: Propylene glycol methyl ether (PM) and butanone are mixed in a mass ratio of 1:1, which is used to adjust the viscosity of the glue and maintain a relatively uniform and stable system.
[0044] Embodiment 1: In some embodiments, a method for preparing a high CTI high thermal conductivity epoxy glass fiber cloth based laminate comprises the following steps:
[0045] Step 1: Prepare glue;
[0046] (1) Preparation of polydopamine-modified nanoparticles
[0047] 55 parts of nano zinc oxide, 110 parts of carbon nanotubes and 48 parts of dextran were mixed, ball-milled at 80°C for 1 hour, and impurity gases were removed by vacuuming; the ball-milled product was placed in 400 parts of deionized water, pressurized to 1 MPa, maintained for 2 minutes, and then returned to normal pressure, then reduced to 0.3 MPa, maintained for 8 minutes, and then returned to normal pressure, and then heated to 65°C by microwave-assisted heating, 400 parts of Tris-HCl buffer and 350 parts of dopamine hydrochloride were added, and the pH value was adjusted to 9.1 with NaOH; heated and stirred at 55°C for 8 hours, and polydopamine-modified nanoparticles were obtained after centrifugal washing and drying;
[0048] (2) 800 parts of solvent (PM and butanone mixed in a mass ratio of 1:1) were added into the reactor, and stirring was started at a speed of 500 r / min;
[0049] (3) Resin tank: 500 parts of phenoxy resin with a molecular weight of 30,000 to 50,000, 85 parts of fluorinated polyimide, 102 parts of brominated epoxy resin and 70 parts of EPDM rubber are injected into the reactor;
[0050] (4) Cross-linking reaction: 8 parts of a cross-linking curing agent (mixed with polyformaldehyde and dicyclopentadiene resin in a mass ratio of 1:0.8) and 5 parts of an accelerator were added to a reactor, the reaction temperature was controlled at 55°C, and the reaction was continued with high-speed stirring for 1.5 hours, then the temperature was raised to 60°C, and the reaction was continued with high-speed stirring for 1 hour to allow the cross-linking reaction to fully occur with the above-mentioned resin;
[0051] (5) Stop the machine to measure S / G: Draw an appropriate amount of glue liquid and test the S / G of the glue: 230~270S, the glue quality is qualified;
[0052] Step 2: Impregnation;
[0053] The electronic-grade glass fiber cloth is placed on the cloth rack of the impregnation machine, and its advancement is controlled by tension. The electronic-grade glass fiber cloth passes through the impregnation tank with glue, and the electronic-grade glass fiber cloth soaked in glue enters the oven. The oven temperature is controlled to be 180°C, and the excess solvent is volatilized and the resin and the cross-linking curing agent are further reacted to obtain a prepreg with appropriate parameters;
[0054] Step 3: Surface pretreatment of the prepreg;
[0055] The semi-cured sheet was placed in an alkaline treatment solution and ultrasonically treated for 1 hour at a temperature of 30°C and normal pressure, and then washed with water and dried.
[0056] Step 4: Stacking;
[0057] Multiple prepregs are stacked, covered with copper foil on one or both sides, and then combined and sent to the hot press.
[0058] Step 5: Pressing;
[0059] The hot press is used for lamination (temperature 210℃, pressure 3.5Mpa), the resin in the prepreg is melted by high temperature, and the bubbles are driven out under high pressure and the resin is completely solidified, completing the strong bonding between the PP sheets and the copper foil. According to the diffusion principle, this bonding is achieved through the mutual diffusion and penetration between the macromolecules on the interface, and then the interweaving is produced.
[0060] Step 6: Cutting;
[0061] The edge material of the laminated substrate is cut off, and then after passing the appearance, thickness and other inspections, a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate is obtained.
[0062] Embodiment 2: In some embodiments, a method for preparing a high CTI high thermal conductivity epoxy glass fiber cloth based laminate comprises the following steps:
[0063] Step 1: Prepare glue;
[0064] (1) Preparation of polydopamine-modified nanoparticles
[0065] 83 parts of nano zinc oxide, 100 parts of carbon nanotubes and 70 parts of dextran were mixed, ball-milled at high temperature of 50°C for 2 hours, and impurity gases were removed by vacuuming; the ball-milled product was placed in 300 parts of deionized water, pressurized to 1.5 MPa, maintained for 1 minute and then returned to normal pressure, then reduced to 0.5 MPa, maintained for 5 minutes and then returned to normal pressure, and then heated to 84°C by microwave-assisted heating, 400 parts of Tris-HCl buffer and 350 parts of dopamine hydrochloride were added, and the pH value was adjusted to 9.1 with NaOH; heated and stirred at 55°C for 8 hours, and polydopamine-modified nanoparticles were obtained after centrifugal washing and drying;
[0066] (2) 980 parts of solvent (PM and butanone mixed in a mass ratio of 1:1) were added into the reactor, and stirring was started at a speed of 800 r / min;
[0067] (3) Resin tank: 625 parts of phenoxy resin with a molecular weight of 30,000 to 50,000, 45 parts of fluorinated polyimide, 165 parts of brominated epoxy resin and 50 parts of EPDM rubber are injected into the reactor;
[0068] (4) Cross-linking reaction: 13 parts of a cross-linking curing agent (a mixture of polyformaldehyde and dicyclopentadiene resin in a mass ratio of 1:0.5) and 10 parts of an accelerator were added to a reactor, the reaction temperature was controlled at 60°C, and the reaction was continued with high-speed stirring for 2 hours, then the temperature was raised to 65°C, and the reaction was continued with high-speed stirring for 1.5 hours to allow the cross-linking reaction to fully occur with the above-mentioned resin;
[0069] (5) Stop the machine to measure S / G: Draw an appropriate amount of glue liquid and test the S / G of the glue: 230~270S, the glue quality is qualified;
[0070] Step 2: Impregnation;
[0071] The electronic-grade glass fiber cloth is placed on the cloth rack of the impregnation machine, and its advancement is controlled by tension. The electronic-grade glass fiber cloth passes through the impregnation tank with glue, and the electronic-grade glass fiber cloth soaked in glue enters the oven. The oven temperature is controlled to be 200°C, and the excess solvent is volatilized and the resin and the cross-linking curing agent are further reacted to obtain a prepreg with appropriate parameters;
[0072] Step 3: Surface pretreatment of the prepreg;
[0073] The semi-cured sheet was placed in an alkaline treatment solution and ultrasonically treated for 2 hours at a temperature of 25°C and normal pressure, and then washed with water and dried.
[0074] Step 4: Stacking;
[0075] Multiple prepregs are stacked, covered with copper foil on one or both sides, and then combined and sent to the hot press.
[0076] Step 5: Pressing;
[0077] The hot press is used for lamination (temperature 230℃, pressure 2.3Mpa), the resin in the prepreg is melted by high temperature, and the bubbles are driven out under high pressure and the resin is completely solidified, completing the strong bonding between the PP sheets and the copper foil. According to the diffusion principle, this bonding is achieved through the mutual diffusion and penetration between the macromolecules on the interface, and then the interweaving is produced.
[0078] Step 6: Cutting;
[0079] The edge material of the laminated substrate is cut off, and then after passing the appearance, thickness and other inspections, a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate is obtained.
[0080] Embodiment 3: In some embodiments, a method for preparing a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate comprises the following steps:
[0081] Step 1: Prepare glue;
[0082] (1) Preparation of polydopamine-modified nanoparticles
[0083] 75 parts of nano zinc oxide, 106 parts of carbon nanotubes and 55 parts of dextran were mixed, ball-milled at 62°C for 1.5 hours, and impurity gases were removed by vacuuming; the ball-milled product was placed in 320 parts of deionized water, pressurized to 1.2 MPa, maintained for 1 minute, and then returned to normal pressure, then reduced to 0.4 MPa, maintained for 6 minutes, and then returned to normal pressure, and then heated to 74°C by microwave-assisted heating, 400 parts of Tris-HCl buffer and 360 parts of dopamine hydrochloride were added, and the pH value was adjusted to 8.8 with NaOH; heated and stirred at 62°C for 5 hours, and polydopamine-modified nanoparticles were obtained after centrifugal washing and drying;
[0084] (2) 890 parts of solvent (PM and butanone mixed in a mass ratio of 1:1) were added into the reactor, and stirring was started at a speed of 600 r / min;
[0085] (3) Resin tank: 615 parts of phenoxy resin with a molecular weight of 30,000 to 50,000, 75 parts of fluorinated polyimide, 155 parts of brominated epoxy resin and 63 parts of EPDM rubber are injected into the reaction kettle;
[0086] (4) Cross-linking reaction: 10 parts of a cross-linking curing agent (a mixture of polyformaldehyde and dicyclopentadiene resin in a mass ratio of 1:0.7) and 8 parts of an accelerator were added to a reactor, the reaction temperature was controlled at 56°C, and the reaction was continued with high-speed stirring for 1.6 hours, then the temperature was raised to 62°C, and the reaction was continued with high-speed stirring for 1.2 hours to allow the cross-linking reaction to fully occur with the above-mentioned resin;
[0087] (5) Stop the machine to measure S / G: Draw an appropriate amount of glue liquid and test the S / G of the glue: 230~270S, the glue quality is qualified;
[0088] Step 2: Impregnation;
[0089] The electronic-grade glass fiber cloth is placed on the cloth rack of the impregnation machine, and its advancement is controlled by tension. The electronic-grade glass fiber cloth passes through the impregnation tank with glue, and the electronic-grade glass fiber cloth soaked in glue enters the oven. The oven temperature is controlled to be 185°C, and the excess solvent is volatilized and the resin and the cross-linking curing agent are further reacted to obtain a prepreg with appropriate parameters;
[0090] Step 3: Surface pretreatment of the prepreg;
[0091] The semi-cured sheet was placed in an alkaline treatment solution and ultrasonically treated for 1.6 hours at a temperature of 28°C and normal pressure, and then washed with water and dried.
[0092] Step 4: Stacking;
[0093] Multiple prepregs are stacked, covered with copper foil on one or both sides, and then combined and sent to the hot press.
[0094] Step 5: Pressing;
[0095] Use a hot press to press (temperature 215℃, pressure 3.0Mpa), use high temperature to melt the resin in the prepreg, and drive out the bubbles under high pressure and completely solidify the resin, completing the strong bonding between the PP sheets and the copper foil. According to the diffusion principle, this bonding is achieved through the mutual diffusion and penetration between the macromolecules on the interface, and then the interweaving.
[0096] Step 6: Cutting;
[0097] The edge material of the laminated substrate is cut off, and then after passing the appearance, thickness and other inspections, a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate is obtained.
[0098] Comparative Example 1: The difference from Example 3 is that step 3: surface pretreatment of the prepreg is not performed. At the same time, when preparing polydopamine-modified nanoparticles, the following steps are not performed: pressurizing to 1.2 MPa, maintaining for 1 min, then returning to normal pressure, then reducing the pressure to 0.4 MPa, maintaining for 6 min, and then returning to normal pressure.
[0099] Comparative Example 2: The difference from Example 3 is that the polydopamine-modified nanoparticles are replaced by nano zinc oxide.
[0100] Comparative Example 3: The difference from Example 3 is that the preparation method of polydopamine modified nanoparticles is different: 105 parts of nano zinc oxide and 131 parts of carbon nanotubes are mixed, ball-milled at 62°C for 1.5 hours, and impurity gases are removed by vacuum; the ball-milled product is placed in 320 parts of deionized water, pressurized to 1.2 MPa, maintained for 1 minute, and then restored to normal pressure, then reduced to 0.4 MPa, maintained for 6 minutes, and then restored to normal pressure, and then heated to 74°C by microwave-assisted heating, 400 parts of Tris-HCl buffer and 360 parts of dopamine hydrochloride are added, and the pH value is adjusted to 8.8 with NaOH; heated and stirred at 62°C for 5 hours, and polydopamine modified nanoparticles are obtained after centrifugal washing and drying.
[0101] Comparative Example 4: The difference from Example 3 is that the preparation method of polydopamine-modified nanoparticles is different: 75 parts of nano-zinc oxide, 106 parts of carbon nanotubes and 55 parts of dextran are mixed, ball-milled at 62°C for 1.5 hours, and impurity gases are removed by vacuum; the ball-milled product is placed in 320 parts of deionized water, pressurized to 1.2 MPa, maintained for 1 minute, and then restored to normal pressure, then reduced to 0.4 MPa, maintained for 6 minutes, and then restored to normal pressure, and then heated to 74°C by microwave-assisted heating, 400 parts of Tris-HCl buffer and 30 parts of dopamine hydrochloride are added, and the pH value is adjusted to 8.8 with NaOH; heated and stirred at 62°C for 5 hours, and polydopamine-modified nanoparticles are obtained after centrifugal washing and drying.
[0102] Comparative Example 5: The difference from Example 3 is that the cross-linking curing agent is replaced by DICY (dicyandiamide).
[0103] Test Examples The following performance tests were performed on the high CTI and high thermal conductivity epoxy glass fiber cloth-based laminates prepared in Examples 1 to 3 and Comparative Examples 1 to 5:
[0104] Thermal conductivity: ASTM D5470-17.
[0105] Dielectric properties (dielectric constant Dk, dielectric loss Df): IPC-TM-650 2.5.5.9:1998.
[0106] Heat resistance: thermal cracking time T288 / T260: IPC-TM-650 2.4.24.C: 1994; glass transition temperature Tg: IPC-TM-650 2.4.24. Decomposition temperature Td (5%, N2): IPC-TM-650 2.4.24.6: 2006.
[0107] Strength (peel strength, bending strength): GB / T 4723-2017.
[0108] CTI (Current Tracking Index): GB / T 4207-2022.
[0109] Table 1 Performance test results of high CTI high thermal conductivity epoxy glass fiber cloth laminate
[0110] Test items Example 1 Example 2 Example 3 Comparative Example 1 Thermal conductivity 2.97W / mk 2.88W / mk 3.06W / mk 2.93W / mk T288 >80min >80min >80min >70min Dk(10GHZ,R / C50%) 3.3 3.7 3.0 3.4 Df(10GHZ,R / C50%) 0.003 0.002 0.003 0.004 Tg 218℃ 225℃ 221℃ 213℃ <![CDATA[Td(5%,N2)]]> 325℃ 322℃ 323℃ 321℃ Peel strength 3.24N / mm 2.97N / mm 3.16N / mm 1.56N / mm Bending Strength 298.6MPa 315.8MPa 304.2MPa 281.4MPa CTI / 600v Pass Pass Pass Pass
[0111] Table 2 Performance test results of high CTI high thermal conductivity epoxy glass fiber cloth base laminate
[0112] Test items Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Thermal conductivity 2.58W / mk 2.63W / mk 2.74W / mk 2.60W / mk T288 >60min >70min >60min >60min Dk(10GHZ,R / C50%) 4.6 4.0 4.1 3.9 Df(10GHZ,R / C50%) 0.003 0.004 0.005 0.003 Tg 195℃ 208℃ 201℃ 214℃ <![CDATA[Td(5%,N2)]]> 288℃ 306℃ 297℃ 311℃ Peel strength 1.77N / mm 2.89N / mm 1.93N / mm 2.02N / mm Bending Strength 246.6MPa 270.3MPa 265.6MPa 278.5MPa CTI / 600v NG NG NG NG
[0113] The invention firstly mixes nano zinc oxide, carbon nano tubes and dextran and performs ball milling, promotes further fusion of the materials by first pressurizing and then reducing pressure, then reacts with Tris-HCl buffer and dopamine hydrochloride under alkaline conditions, dopamine self-polymerizes under alkaline conditions and modifies nano particles, and cross-linking reactions occur between polydopamine on the surface of the nano particles and the resin system, and between the resin systems, to form a three-dimensional network cross-linking structure; an accelerator and an improved cross-linking curing agent react with the resin system and the polydopamine modified nano particles, the improved cross-linking curing agent reacts with the active functional groups of the polydopamine, and a dicyclopentadiene structure is introduced to further promote the cross-linking reaction between the resin system and the polydopamine, and after curing, the strength of the three-dimensional network structure and the uniformity of filler distribution are further enhanced, and the heat resistance, thermal conductivity and other properties are improved. The epoxy glass fiber cloth-based laminate prepared by the present invention meets the requirements of high CTI (600v), excellent heat resistance, high thermal conductivity (thermal conductivity can reach 3.06W / mk) and low dielectric (dielectric constant Dk is minimum 3.0, dielectric loss Df is minimum 0.002), and has high strength (peel strength is maximum 3.24N / mm, bending strength is maximum 315.8MPa).
[0114] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high CTI and high thermal conductivity epoxy glass fiber cloth based laminate, characterized in that: A resin system is formed by using a phenoxy resin with a molecular weight of 30,000 to 50,000, a fluorinated polyimide, a brominated epoxy resin and EPDM rubber, and polydopamine-modified nanoparticles are added to the resin system as fillers, and then a cross-linking curing agent and an accelerator are added to make glue; then, the glue is impregnated with glass fiber cloth to obtain a semi-cured sheet, and the semi-cured sheet and copper foil are stacked and pressed to obtain a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate; The cross-linking curing agent is prepared by mixing paraformaldehyde and dicyclopentadiene resin in a ratio of 1:0.5-0.8; The polydopamine modified nanoparticles include the following raw materials in parts by weight: 350-400 parts of dopamine hydrochloride, 48-70 parts of dextran, 55-83 parts of nano zinc oxide, and 100-110 parts of carbon nanotubes.
2. The high CTI and high thermal conductivity epoxy glass fiber cloth based laminate according to claim 1, characterized in that: The glue comprises the following raw materials in parts by weight: 500-625 parts of phenoxy resin with a molecular weight of 30,000-50,000, 45-85 parts of fluorine-containing polyimide, 102-165 parts of brominated epoxy resin, 50-70 parts of ethylene propylene rubber, 165-178 parts of polydopamine modified nanoparticles, 8-13 parts of a cross-linking curing agent, 5-10 parts of an accelerator, and 800-980 parts of a solvent.
3. The high CTI and high thermal conductivity epoxy glass fiber cloth based laminate according to claim 1, characterized in that: The preparation method of the polydopamine modified nanoparticles is as follows: nano zinc oxide, carbon nanotubes and dextran are mixed, ball milled at 50-80°C for 1-2h, and impurity gases are removed by vacuuming; the ball milled product is placed in 300-400 parts of deionized water, pressurized to 1-1.5MPa, maintained for 1-2min, and then restored to normal pressure, then reduced to 0.3-0.5MPa, maintained for 5-8min, and then restored to normal pressure, then heated to 65-84°C by microwave-assisted heating, Tris-HCl and dopamine hydrochloride are added, and the pH value is adjusted to 8.3-9.1 by NaOH; heated and stirred at 55-65°C for 4-8h, and the polydopamine modified nanoparticles are obtained after centrifugal washing and drying.
4. A method for preparing a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate according to claim 1, characterized in that: The following steps are involved: Step 1: Prepare glue; (1) Preparation of polydopamine-modified nanoparticles The nano zinc oxide, carbon nanotubes and dextran are mixed, ball milled at 50-80°C for 1-2h, and impurity gases are removed by vacuuming; the ball milled product is placed in 300-400 parts of deionized water, pressurized to 1-1.5MPa, maintained for 1-2min and then restored to normal pressure, then reduced to 0.3-0.5MPa, maintained for 5-8min and then restored to normal pressure, then heated to 65-84°C by microwave-assisted heating, 400 parts of Tris-HCl and dopamine hydrochloride are added, and the pH value is adjusted to 8.3-9.1 with NaOH; heated and stirred at 55-65°C for 4-8h, and polydopamine modified nanoparticles are obtained after centrifugal washing and drying; (2) injecting the solvent into the reaction kettle and starting stirring; (3) Resin feeding tank: Phenoxy resin with a molecular weight of 30,000 to 50,000, fluorinated polyimide, brominated epoxy resin and EPDM rubber are injected into the reaction kettle; (4) Cross-linking reaction: Add the cross-linking curing agent and accelerator into the reaction kettle, control the reaction temperature at 55-60° C., continue to stir at high speed for 1.5-2 hours, then raise the temperature to 60-65° C., continue to stir at high speed for 1-1.5 hours, so that the cross-linking reaction with the above-mentioned resin can be fully produced; Step 2: Impregnation; Step 3: Surface pretreatment of the prepreg; The semi-cured sheet is placed in an alkaline treatment solution and ultrasonically treated for 1 to 2 hours at a temperature of 25 to 30°C and normal pressure, then washed with water and dried; Step 4: Stacking; Stack multiple prepregs, cover one or both sides with copper foil, and send them into a hot press after assembly; Step 5: Pressing; A hot press is used for pressing. The resin in the prepreg is melted by high temperature and the bubbles are driven out under high pressure, so that the resin gradually hardens and adheres to the copper foil.
5. The method for preparing the high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate according to claim 4, characterized in that: Also includes step 6: cropping.
6. The method for preparing the high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate according to claim 5, characterized in that: Step 2 is specifically as follows: placing the electronic-grade glass fiber cloth on the cloth rack of the impregnation machine, controlling its advancement by tension, passing the electronic-grade glass fiber cloth through the impregnation tank with glue, and the electronic-grade glass fiber cloth soaked in glue enters the oven, controlling the oven temperature to 180-200°C, and obtaining a semi-cured sheet after drying.
7. The method for preparing the high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate according to claim 6, characterized in that: The pressing temperature of the hot press is 210-230°C and the pressure is 2.3-3.5Mpa.
8. The method for preparing the high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate according to claim 7, characterized in that: Step 6 is specifically as follows: trimming off the edge material of the laminated substrate, and then obtaining a high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate after the laminate passes the appearance and thickness inspections.
9. The method for preparing the high CTI and high thermal conductivity epoxy glass fiber cloth-based laminate according to claim 8, characterized in that: The method further comprises the step (5) of stopping the machine to measure S / G: extracting a proper amount of glue liquid and testing whether the S / G of the glue is between 230 and 270S. If so, the glue quality is qualified.
10. A high CTI and high thermal conductivity epoxy glass fiber cloth based laminate prepared according to the preparation method of any one of claims 4 to 9.
Citation Information
Cited By
High-thermal-conductivity low-resistance epoxy adhesive solution, preparation method and use thereof
CN122772330A